Neighbourhood walkability and mental health in older adults: A cross-sectional analysis from EpiFloripa Aging Study - Siqueira Junior, Joel de Almeida; Lopes, Adalberto Aparecido dos Santos; Godtsfriedt, Carla Elane Silva; Justina, Marcelo Dutra Della; Paiva, Karina Mary de; d’Orsi, Eleonora; Rech, Cassiano Ricardo (Frontiers in Aging, 2022)
This study aims to analyze the association between walkability index and depressive symptoms and cognitive impairment and test the mediating role of moderate-vigorous physical activity (MVPA) in this relationship among older adults from Florianópolis, Brazil. This is cross-sectional research with data from the third wave of the EpiFloripa Aging cohort study, conducted in 2017-2019. Depressive symptoms were assessed using the short version of the Geriatric Depression Scale (GDS), and cognitive impairment, using the Mini-Mental State Examination (MMSE) scales. The neighbourhood environment was assessed using a walkability index, which considered 500-meter network buffers around the participants' homes. Binary logistic regression analysis the association between the walkability index (quartile) and mental health outcomes (yes vs no). Structural equation modelling evaluated the mediation between the walkability index and cognitive impairment by MVPA with an estimator of dichotomous variables. 1,162 people participated in the study (61.5% women, average age = 73.1). Older adults residing in places with a high and highest walkability index were 38% and 44% less likely to have cognitive impairment, respective. There was no association between depressive symptoms and walkability index in crude nor adjusted analysis. Engaging in MVPA had a partial but not significant effect (14%; p = 0.087), showing a tendency for this relationship to be partially explained by the greater engagement in physical activities in places with greater walkability. Policy planning to prevent and reduce the risks of cognitive impairment should consider factors of the physical environment as determinants in older adults.